2018
DOI: 10.1002/biof.1433
|View full text |Cite
|
Sign up to set email alerts
|

MANF attenuates neuronal apoptosis and promotes behavioral recovery via Akt/MDM‐2/p53 pathway after traumatic spinal cord injury in rats

Abstract: The aim of this study was to investigate the potential effect and mechanism of action of MANF in attenuating neuronal apoptosis following t-SCI. A clip compressive model was used to induce a crush injury of the spinal cord in a total of 230 rats. The Basso, Beattie, and Bresnahan (BBB) score, spinal cord water content, and blood spinal cord barrier (BSCB) permeability were evaluated. The expression levels of MANF and its downstream proteins were examined by western blotting. Immunofluorescence staining of MANF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Apart from neuronal apoptosis, t-SCI also induces edema and BSCB breakdown, which are the major pathological changes and contribute to a poor prognosis (Gao et al, 2018). In the clip compressive model of t-SCI, the compression forces applied to spinal cord can mutilate blood vessels, damage cellular components, and breakdown BSCB (Casella et al, 2006; Dulmovits and Herman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from neuronal apoptosis, t-SCI also induces edema and BSCB breakdown, which are the major pathological changes and contribute to a poor prognosis (Gao et al, 2018). In the clip compressive model of t-SCI, the compression forces applied to spinal cord can mutilate blood vessels, damage cellular components, and breakdown BSCB (Casella et al, 2006; Dulmovits and Herman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations have suggested that cell necrosis is the predominant landmark of SCI [ 43 , 44 ]. Also, reports claim that resulting necrosis and inflammation of the spinal cord associated neurons after primary mechanical damage are linked with apoptosis [ 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether MANF is mainly expressed in neurons and to determine its subcellular localization, we performed double immunofluorescence labeling of MANF/neuronal nuclei (NeuN) and MANF/GRP78 as previously described ( Shen et al, 2012 ; Gao et al, 2018 ; Herranen et al, 2020 ), with minor modifications to the protocol. The following antibodies were used: rabbit polyclonal anti-MANF (1:400 dilution); mouse monoclonal anti-NeuN (clone A60, cat.…”
Section: Methodsmentioning
confidence: 99%